2014
DOI: 10.1016/j.vaccine.2014.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the efficacy of monovalent and tetravalent dengue vaccine formulations against DENV-4 challenge in AG129 mice

Abstract: Dengue (DEN) is the most important mosquito-borne viral disease, with a major impact on global health and economics, caused by four serologically and distinct viruses termed DENV-1 to DENV-4. Currently, there is no licensed vaccine to prevent DEN. We have developed a live attenuated tetravalent DENV vaccine candidate (TDV) (formally known as DENVax) that has shown promise in preclinical and clinical studies and elicits neutralizing antibody responses to all four DENVs. As these responses are lowest to DENV-4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Recently, this 703-4 model was used to evaluate a candidate live attenuated dengue vaccine. The tetravalent dengue vaccine reduced viraemia and protected mice against lethal 703-4 challenge (Fuchs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this 703-4 model was used to evaluate a candidate live attenuated dengue vaccine. The tetravalent dengue vaccine reduced viraemia and protected mice against lethal 703-4 challenge (Fuchs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the use of immunocompromised mice is a factor that affects the course of disease and evaluation of vaccines. Specifically, studies with live vaccines have shown that AG129 mice generate protective responses [88][89][90]. However, AG129 mice are lacking aspects of cellular immunity that appear to impact their ability to produce protection following immunization with a non-replicating vaccine [93].…”
Section: Discussionmentioning
confidence: 99%
“…TDV was recently tested against lethal challenge with the disseminated DENV-4 703–4 model in AG129 mice [89]. Mice immunized with a single dose of TDV, monovalent TDV-4 or monovalent TDV-2 survived lethal challenge, but all control mice succumbed to infection by day 8.…”
Section: Vaccine Testing In Dengue Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model, neutralizing antibodies induced by TDV neutralized a number of contemporary DENV-4 isolates from different geographical locations and DENV-4 genotypes [45]. TDV vaccination provided partial protection against mortality and signs of morbidity following DENV-4 challenge in AG129 mice [45].…”
Section: Dengue-dengue Chimera (Tdv)mentioning
confidence: 99%